KEPUTUSAN TRANSFER PRICING BERDASARKAN PAJAK,TUNNELING DAN EXCHANGE RATE (SEBUAH ANALISIS DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Ariyanto, Rico Dwi; Mujiyati, Mujiyati (ITB AAS Indonesia Surakarta, 2024)
Transfer Pricing is the company's policy in determining the transfer price of a transaction, be it goods, services, intangible assets, or financial transactions carried out by the company between parties who have a special relationship. This study aims to find out and analyze the influence of taxes, tunneling and exchange rates on manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used was purposive sampling, which was obtained by 19 companies. From the sample, observation data for five years was 95. The analysis method used is logistic regression analysis. The results of the study provide empirical evidence that the results of the study show that taxes, tunneling and exchange rates have no effect on the company's decision to transfer pricing Keywords : tax, tunneling, exchange rate, transfer pricing